2019
DOI: 10.1080/17445647.2019.1657510
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution bathymetry of the Alderney Race and its geological and sedimentological description (Raz Blanchard, northwest France)

Abstract: We present a high-resolution 1:15,000 bathymetric map (Main map) of Alderney Race located offshore of northwestern France, with the strongest currents in Europe. We use this map, underwater video transects and Shipek grabs to improve geological maps previously published. We distinguished Proterozoic crystalline rocks, Paleozoic and Cretaceous sedimentary rocks on the present-day sea floor. Some structures as faults and folds are also mapped. We identified a Quaternary cover made of pebbles, boulders and blocks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…Ikhennicheu et al [15] studied the wake of various elementary obstacles used to experimentally reproduce bathymetry variations, like those encountered in the Alderney Race in the middle of the English Channel. Such bathymetry variations have been observed in-situ, according to the geological description of this particular place presented by Furgerot et al [7]. They concluded that a unique and wide obstacle, i.e.…”
Section: Introductionmentioning
confidence: 57%
“…Ikhennicheu et al [15] studied the wake of various elementary obstacles used to experimentally reproduce bathymetry variations, like those encountered in the Alderney Race in the middle of the English Channel. Such bathymetry variations have been observed in-situ, according to the geological description of this particular place presented by Furgerot et al [7]. They concluded that a unique and wide obstacle, i.e.…”
Section: Introductionmentioning
confidence: 57%
“…Ikhennicheu et al [23] present a case study comparison of various elementary obstacles used to reproduce bathymetry variations, like those encountered in the Alderney Race (middle of the English Channel), as shown by its geological description by Furgerot et al [24]. They concluded that wide obstacles (6 times wider than its height) produces the most energetic wake that extends up to the free surface.…”
Section: Introductionmentioning
confidence: 99%
“…However, two conditions obliged us to change the location. A preliminary study revealed that, in the northern sector, the seafloor is mostly composed of Proterozoic crystalline rocks that exhibit a dense fracture network and form a highly irregular topography [15]. Therefore, our ADCP support platforms were thought to be more unstable there.…”
Section: Data and Methodsof Analysis (A) Static Point Velocity Measurmentioning
confidence: 99%
“…According to a numerical study by Coles et al [13], the maximum power that can be extracted in this shallow water 15km-wide strait, is estimated at 5.1 GW, which is 35% more than a previous estimate proposed by Draper et al [14] for the Pentland Firth (UK). The complexity of local hydrodynamics and the interaction between the highly irregular bottom topography [15], powerful tidal stream and high waves was highlighted in a number of numerical studies devoted to this geographic area (e.g. [16][17][18]).…”
Section: Introductionmentioning
confidence: 99%